Resin powder and its manufacturing method
The resin powder with controlled particle size and roundness, along with specific saponification, addresses clogging issues in PVA-containing powders by enhancing permeability and fluidity, especially in humid environments.
Patent Information
- Application Number
- JP2021537012
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-30
- Filing Date
- 2020-07-27
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-07-27
AI Technical Summary
Resin powders containing polyvinyl alcohol (PVA) tend to clog pipes and silos, particularly in humid environments due to their water solubility and hygroscopicity, leading to operational inefficiencies.
The development of resin powder with a specific particle size, roundness, and saponification degree, characterized by an average particle size of 100 to 2,000 μm, a roundness of 0.1 to 0.8, and a saponification degree of 35 to 99.99 mol%, ensuring a high content of particles between 100 to 1,000 μm, and a product of roundness and saponification exceeding 18 mol%, which enhances permeability.
The resin powder exhibits improved passageability through pipes and silos, reducing clogging issues and maintaining fluidity even in humid conditions.
Smart Images

Figure 0007620553000001 
Figure 0007620553000002 
Figure 0007620553000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin powder and a method for producing the same. [Background technology]
[0002] Polyvinyl alcohol polymer (hereinafter referred to as "PVA") is a synthetic resin obtained by saponifying polyvinyl ester. PVA is water-soluble and is used as a synthetic fiber raw material, a film raw material, an emulsifying dispersant, an adhesive, etc.
[0003] PVA-containing resin powders are usually obtained by pulverizing a solid PVA obtained through saponification, etc. For example, in Patent Document 1, a PVA powder with a controlled particle size is obtained by changing the size of the sieve at the outlet of a pulverizer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2015 / 186745 Summary of the Invention [Problem to be solved by the invention]
[0005] Resin powder is transported through pipes and packed in bags through silos within factories, etc. However, during these operations, resin powder containing PVA may clog pipes, silos, etc. Resin powder containing PVA is prone to clogging, especially in humid environments, possibly due to the water solubility and hygroscopicity of PVA.
[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a resin powder that has excellent passability through pipes and silos, and a method for producing such a resin powder. [Means for solving the problem]
[0007] The above objectives are: [1] A resin powder containing a vinyl alcohol polymer, having an average particle size of 100 to 2,000 μm, and having an average value PA of the roundness P represented by the following formula (1) of 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm, of 0.1 to 0.8;
number
[0008] According to the present invention, it is possible to provide a resin powder having excellent passability through pipes and silos, and a method for producing such a resin powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Resin powder> The resin powder of the present invention contains a vinyl alcohol polymer (PVA: polyvinyl alcohol), has an average particle size of 100 to 2,000 μm, and has an average value PA of roundness P (hereinafter also referred to as "average roundness") represented by the following formula (1) of 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm, of 0.1 to 0.8.
[0010] In this specification, a numerical range described using "to" means that the numerical range includes the numerical values before and after "to" as the lower limit and upper limit.
[0011] The resin powder of the present invention, particularly since the average roundness is within the above-mentioned specific range, is less likely to clog pipes or silos when transported through pipes or packed in bags through a silo, compared with conventional resin powders. The reason for this is not entirely clear, but it is presumed that the rounded corners of each particle reduce friction when the particles come into contact with each other or with a wall surface, etc., resulting in improved particle flowability.
[0012] PVA is usually the main component of the resin powder of the present invention. The main component refers to the component with the highest content by mass. The lower limit of the content of PVA in the nonvolatile content of the resin powder of the present invention is preferably 50 mass%, more preferably 70 mass%, even more preferably 90 mass%, and even more preferably 99 mass%. The upper limit of the content of PVA in the nonvolatile content of the resin powder of the present invention may be 100 mass%. Nonvolatile components other than PVA that may be contained in the resin powder of the present invention include resins other than PVA, surfactants, additives such as plasticizers, and various compounds used during production. In addition, the content of volatile components in the resin powder of the present invention is usually 20 mass% or less, preferably 15 mass% or less, and more preferably 10 mass% or less. Examples of volatile components that may be contained in the resin powder of the present invention include alcohol, water, and the like.
[0013] PVA is a polymer having vinyl alcohol units as monomer units. PVA is usually obtained by saponifying polyvinyl ester. The lower limit of the proportion of vinyl alcohol units in the total monomer units in PVA is preferably 35 mol%, more preferably 50 mol%, even more preferably 70 mol%, and in some cases even more preferably 80 mol% or 90 mol%. By making the proportion of vinyl alcohol units equal to or greater than the above lower limit, the passability is improved, particularly in a high humidity environment, and the resin powder of the present invention can be efficiently produced by a production method involving crushing and surface treatment. On the other hand, the upper limit of the proportion of the vinyl alcohol units may be 100 mol%, but is preferably 99.99 mol%, more preferably 99 mol%.
[0014] The lower limit of the saponification degree of PVA is preferably 35 mol%, more preferably 50 mol%, even more preferably 70 mol%, and even more preferably 80 mol% or 90 mol%. By setting the saponification degree to be equal to or higher than the above lower limit, the passability is improved, particularly in a high humidity environment, and the resin powder of the present invention can be efficiently produced by a production method involving crushing and surface treatment. On the other hand, the upper limit of the saponification degree may be 100 mol%, but is preferably 99.99 mol%, and more preferably 99 mol%. The saponification degree is a value measured by the method described in JIS K6726:1994.
[0015] PVA may have other monomer units other than vinyl alcohol units and vinyl ester units. Examples of monomers that provide the other monomer units include α-olefins such as ethylene, propylene, 1-butene, isobutene, and 1-hexene; acrylic acid, methacrylic acid; acrylic acid esters such as methyl acrylate and ethyl acrylate; methacrylic acid esters such as methyl methacrylate and ethyl methacrylate; acrylamide derivatives such as N-methylacrylamide and N-ethylacrylamide; methacrylamide derivatives such as N-methylmethacrylamide and N-ethylmethacrylamide; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, and n-butyl vinyl ether; and hydroxyl groups such as ethylene glycol vinyl ether, 1,3-propanediol vinyl ether, and 1,4-butanediol vinyl ether. Containing vinyl ether; allyl acetate; allyl ether such as propyl allyl ether, butyl allyl ether, hexyl allyl ether; monomers having an oxyalkylene group; isopropenyl acetate; hydroxyl group-containing α-olefins such as 3-buten-1-ol, 4-penten-1-ol, 5-hexen-1-ol, 7-octen-1-ol, 9-decen-1-ol, 3-methyl-3-buten-1-ol; monomers having a silyl group such as vinyl trimethoxysilane, vinyl methyl dimethoxysilane, vinyl dimethyl methoxysilane, vinyl triethoxysilane, vinyl methyl diethoxysilane, vinyl dimethyl ethoxysilane, 3-(meth)acrylamidopropyl trimethoxysilane, 3-(meth)acrylamidopropyl triethoxysilane, etc. Among these, α-olefins, acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are preferred.
[0016] The proportion of the other monomer units in the total monomer units in the PVA may be preferably 20 mol % or less, more preferably 10 mol % or less, whereas the proportion of the other monomer units may be, for example, 0.1 mol % or more, or 1 mol % or more.
[0017] The viscosity average degree of polymerization of PVA is not particularly limited, but is preferably 200 or more, more preferably 250 or more, even more preferably 400 or more, and particularly preferably 600 or more. The viscosity average degree of polymerization is preferably 5,000 or less, more preferably 4,500 or less, and even more preferably 3,500 or less. By setting the viscosity average degree of polymerization within the above range, industrial production of resin particles having the above average roundness becomes easy. The viscosity average degree of polymerization is a value measured in accordance with JIS K6726:1994. That is, the viscosity average degree of polymerization can be calculated from the intrinsic viscosity [η] (unit: liter / g) measured in water at 30°C after resaponifying PVA to a saponification degree of 99.5 mol% or more and purifying it, according to the following formula. Viscosity average degree of polymerization=([η]×10 4 / 8.29) (1 / 0.62)
[0018] The lower limit of the average particle diameter of the resin powder of the present invention is 100 μm, preferably 150 μm, and more preferably 300 μm. By making the average particle diameter equal to or greater than the lower limit, dust explosions are less likely to occur, and safety can be improved. The upper limit of the average particle diameter is 2,000 μm, preferably 1,500 μm, more preferably 1,000 μm, and even more preferably 850 μm. By making the average particle diameter equal to or less than the upper limit, the fluidity of the particles can be increased, and passability can be improved.
[0019] The average particle size of the resin powder is a value measured in accordance with the method described in JIS K7369:2009.
[0020] The average roundness of the resin powder of the present invention (the average value PA of the roundness P of 50 particles randomly extracted from particles having a particle diameter of 100 to 1,000 μm) is 0.1 or more, preferably 0.15 or more, more preferably 0.2 or more, even more preferably more than 0.2, particularly preferably 0.22 or more, and sometimes extremely preferably 0.25 or more. By setting the average roundness to the above lower limit or more, the fluidity of the particles can be increased and the passability can be improved. On the other hand, the above average roundness is 0.8 or less, preferably 0.7 or less. By setting the average roundness to the above upper limit or less, the productivity of the resin powder of the present invention can be increased. In addition, a resin powder having an average roundness of the above upper limit or less can be effectively produced by a production method that involves crushing and surface treatment.
[0021] The average roundness of the resin powder can be determined by the following method. 50 particles are randomly extracted from the particles having a particle diameter of 100 to 1,000 μm (specifically, a particle diameter of 106 to 1,000 μm) in the resin powder. The particles having a particle diameter of 100 to 1,000 μm can be selected as particles that pass through a sieve mesh with a nominal opening of 1,000 μm (16 mesh) and do not pass through a sieve mesh with a nominal opening of 106 μm (150 mesh) in sieving. The mechanical sieving can be performed, for example, by the method described in JIS K7369:2009. For one extracted particle, the radius of curvature r i Extract the 8 smallest corners (if there are less than 8 corners, all of them) and calculate the radius of curvature r i Based on the projection that maximizes the apparent area, the radius R of the maximum inscribed circle of the particle is measured. The number of corners that the particle has is N (if the particle has 9 or more corners, N is 8), and the measured r i Based on and R, the roundness P of a particle is calculated by the following formula (1): A low roundness P indicates that the particle has many sharp corners, and a high roundness P indicates that the particle is rounded.
[0022]
number
[0023] The above-mentioned roundness P measurement is carried out for the extracted 50 particles, and the average value PA of the roundness P of these 50 particles is calculated. This average value PA is the average roundness.
[0024] In the resin powder of the present invention, the content of particles having a particle diameter of 100 to 1,000 μm (specifically, a particle diameter of 106 to 1,000 μm) is not particularly limited, but is preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more. On the other hand, the upper limit of the content of particles having a particle diameter of 100 to 1,000 μm may be 100% by mass. By having the content of particles having a particle diameter of 100 to 1,000 μm within the above range, the passability is further improved. The content of particles having a particle diameter of 100 to 1,000 μm in the resin powder can be determined according to the method described in JIS K7369:2009 using a sieve mesh with a nominal mesh size of 1,000 μm (16 mesh) and a sieve mesh with a nominal mesh size of 106 μm (150 mesh).
[0025] The resin powder of the present invention preferably satisfies the following formula (2), and more preferably satisfies the following formula (2) and has an average particle size of 100 to 1,000 μm. In such a case, the permeability can be increased, particularly under high humidity. According to the study by the present inventors, the higher the average roundness, the higher the passability tends to be. On the other hand, particularly under high humidity, the passability of a resin powder containing PVA with a low degree of saponification is likely to decrease, possibly due to the influence of hygroscopicity. Therefore, by setting the product (PA×S) of the average value PA (average roundness) of the roundness P and the saponification degree S of PVA to a predetermined value or more, good permeability can be exhibited even under high humidity. PA×S≧18 (2) In formula (2), PA is the average value of the roundness P. S is the degree of saponification (mol%) of PVA.
[0026] The product (PA×S) of the average value PA (average roundness) of the roundness P and the saponification degree S of the PVA is more preferably 19 mol% or more, and even more preferably 20 mol% or more. On the other hand, the upper limit of this product (PA×S) may be, for example, 80 mol% or 60 mol%.
[0027] The angle of repose measured after conditioning the resin powder of the present invention in an atmosphere of 20°C and 30%RH for one week is preferably less than 38°, more preferably less than 35°. The angle of repose measured after conditioning the resin powder of the present invention in an atmosphere of 20°C and 65%RH for one week is preferably less than 40°, more preferably less than 38°. When the angle of repose of the resin powder of the present invention is so low, it can exhibit excellent passability even in a high humidity environment. The lower limit of these angles of repose may be, for example, 25° or 30°. The angle of repose of the resin powder is a value measured according to the method described in JIS 9301-2-2:1999.
[0028] The resin powder of the present invention can be used for various applications, examples of which are given below, but are not limited thereto. (1) Vinyl chloride dispersant Uses: Dispersion stabilizer and dispersion aid for suspension polymerization of vinyl chloride and vinylidene chloride (2) Coating applications: sizing agents, textile processing agents, leather finishing agents, paints, anti-fogging agents, metal corrosion inhibitors, zinc plating gloss agents, antistatic agents (3) Adhesive and binder applications: adhesives, pressure sensitive adhesives, remoisturizing adhesives, various binders, additives for cement and mortar (4) Dispersion stabilizer Applications: Dispersion stabilizer for organic and inorganic pigments in paints and adhesives, etc., dispersion stabilizer for emulsion polymerization of various vinyl compounds, post-emulsifier for bitumen, etc. (5) Paper processing applications: paper strength enhancers, oil and solvent resistance agents, smoothness improvers, surface gloss improvers, sealing agents, barrier agents, light resistance agents, water resistance agents, dye and developer dispersants, adhesion improvers, binders (6) Agricultural uses: pesticide binders, pesticide spreaders, agricultural coating agents, soil conditioners, erosion prevention agents, pesticide dispersants (7) Medical and cosmetic applications: granulation binders, coating agents, emulsifiers, patches, binding agents, film preparation base materials, film-forming agents (8) Viscosity modifier Uses: Thickener, rheology modifier (9) Flocculant Uses: Flocculant for suspended and dissolved matter in water, metal flocculant (10) Film applications: water-soluble film, polarizing film, barrier film, film for packaging textile products, seed protection sheet, vegetation sheet, seed tape, hygroscopic film (11) Molding applications: fibers, pipes, tubes, leak-proof membranes, water-soluble fibers for chemical races, sponges (12) Resin raw material applications: raw material for polyvinyl butyral, raw material for photosensitive resin, raw material for graft polymer, raw material for various gels (13) Post-reaction applications: Post-reaction applications with low molecular weight organic compounds, high molecular weight organic compounds, and inorganic compounds
[0029] <Method of manufacturing resin powder> The method for producing the resin powder of the present invention is not particularly limited, but the following method is preferable. That is, the method for producing the resin powder of the present invention is A step (step B) of obtaining a coarse powder by pulverizing a resin solid material containing PVA; and A step of processing the surface of the coarse powder (step C) Equipped with.
[0030] The method for producing a resin powder of the present invention may further include a step (step A) of synthesizing PVA and obtaining a resin solid material containing PVA.
[0031] (Process A) Step A can include, for example, a polymerization step, a saponification step, and the like.
[0032] In the polymerization step, vinyl ester monomers are polymerized to obtain vinyl ester polymers. Methods for polymerizing vinyl ester monomers include known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Among these methods, bulk polymerization carried out without a solvent and solution polymerization carried out using a solvent such as alcohol are preferred, and solution polymerization carried out in the presence of a lower alcohol is more preferred. As the lower alcohol, alcohols having 3 or less carbon atoms are preferred, methanol, ethanol, n-propanol, and isopropanol are more preferred, and methanol is even more preferred. When carrying out a polymerization reaction by the bulk polymerization method or solution polymerization method, either a batch method or a continuous method can be adopted as the reaction method.
[0033] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Of these, vinyl acetate is preferred.
[0034] Examples of initiators used in the polymerization reaction include known initiators such as azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), etc.; and organic peroxide initiators such as benzoyl peroxide, n-propyl peroxycarbonate, etc. The polymerization temperature when carrying out the polymerization reaction is not particularly limited, but is suitably in the range of 5°C to 200°C.
[0035] When polymerizing the vinyl ester monomer, a copolymerizable monomer can be further copolymerized within the scope of the present invention. When polymerizing the vinyl ester monomer, a chain transfer agent may be used in order to adjust the degree of polymerization of the resulting PVA. Examples of the chain transfer agent include aldehydes such as acetaldehyde, propionaldehyde, butylaldehyde, and benzaldehyde; ketones such as acetone, methyl ethyl ketone, hexanone, and cyclohexanone; mercaptans such as 2-hydroxyethanethiol; thiocarboxylic acids such as thioacetic acid; and halogenated hydrocarbons such as trichloroethylene and perchloroethylene. Among these, aldehydes and ketones are preferably used. The amount of the chain transfer agent to be added is determined according to the chain transfer constant of the chain transfer agent to be added and the degree of polymerization of the desired PVA, but is generally preferably 0.1 to 10% by mass based on the vinyl ester to be used.
[0036] In the saponification step, the vinyl ester polymer is saponified in an alcohol solution using an alkali catalyst or an acid catalyst to obtain PVA. The saponification reaction of the vinyl ester polymer can be carried out by alcoholysis or hydrolysis using a conventionally known basic catalyst such as sodium hydroxide, potassium hydroxide, or sodium methoxide, or an acid catalyst such as p-toluenesulfonic acid. Examples of the solvent used in the saponification reaction include alcohols such as methanol and ethanol; esters such as methyl acetate and ethyl acetate; ketones such as acetone and methyl ethyl ketone; and aromatic hydrocarbons such as benzene and toluene. These can be used alone or in combination of two or more. Among these, it is preferable to use methanol or a mixed solution of methanol and methyl acetate as a solvent and carry out the saponification reaction in the presence of sodium hydroxide, which is a basic catalyst, because it is simple.
[0037] The saponification step can be carried out in a belt reactor, a kneader reactor, a tower reactor, or the like. Through the saponification step, a resin solid containing PVA is obtained. The content of PVA in the non-volatile content of the resin solid is, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and in some cases even more preferably 99% by mass or more. The non-volatile content of this resin solid may be substantially composed of PVA as the main component, but may also contain impurities such as sodium acetate, by-products, and the like.
[0038] (Process B) In step B, the resin solid containing PVA is pulverized. This results in a coarse powder containing PVA. The pulverization can be performed by a known pulverizer. As the pulverizer, a device capable of controlling the degree of pulverization such as pulverization strength is preferable in order to adjust the average particle size of the obtained coarse powder and ultimately the resin powder. In addition to adjusting the pulverization strength, the average particle size of the obtained coarse powder can also be controlled by the processing time. The obtained coarse powder may be subjected to a saponification treatment again. The obtained coarse powder may also be subjected to a washing treatment to reduce impurities such as sodium acetate, by-products, etc., and a drying treatment to reduce volatile content. The resin solid before pulverization may be subjected to a washing treatment or a drying treatment.
[0039] (Process C) In step C, the surface of the coarse powder is processed. When a resin solid containing PVA is crushed, the resulting coarse powder has very sharp corners. Therefore, step C rounds the corners, and a resin powder having an average roundness within a specified range can be efficiently obtained.
[0040] The apparatus used in step C is not particularly limited as long as it can polish the surface of the coarse powder, but examples thereof include a rotary kiln in which a container filled with powder rotates and the powder comes into contact with each other, thereby polishing the surface, a planetary motion mixer capable of imparting three-dimensional motion to the contents by a screw blade that rotates around itself and revolves in the container, and a mixer in which a paddle or screw in the container rotates and polishes the internal powder by the rotation. Examples of the mixer include a high-speed mixer, a Henschel mixer, a turbulizer, and a Loedige mixer. Among these, from the viewpoint of processing efficiency, a mixer is preferred, and a turbulizer and a Loedige mixer are more preferred. In step C, the surface of the coarse powder may be processed while being heated.
[0041] The method for producing a resin powder of the present invention may further include a sieving step for adjusting the average particle size, etc. After step C, a washing treatment and a drying treatment may be performed. EXAMPLES
[0042] The present invention will be described in detail with reference to the following examples, but the present invention is not limited to these examples. The evaluation methods used in the following examples and comparative examples are shown below.
[0043] [Viscosity average degree of polymerization of PVA] The viscosity-average degree of polymerization of PVA was measured in accordance with JIS K6726: 1994. Specifically, when the degree of saponification of PVA was less than 99.5 mol%, it was saponified until the degree of saponification reached 99.5 mol% or more, and the viscosity-average degree of polymerization of the obtained PVA was calculated by the following formula using the intrinsic viscosity [η] (liter / g) measured in water at 30°C. Viscosity average degree of polymerization=([η]×10 4 / 8.29) (1 / 0.62)
[0044] [Saponification degree of PVA] The degree of saponification of PVA (including modified PVA) was determined by the method described in JIS K6726:1994.
[0045] [Average particle size of resin powder and content of particles with a particle size of 100 to 1,000 μm] Using a JIS standard sieve, the average particle size of the resin powder and the content of particles with a particle size of 100 to 1,000 μm (specifically, a particle size of 106 to 1,000 μm) were determined according to the method described in JIS K7369:2009.
[0046] [Average roundness of resin powder] Particles with a particle diameter of 100 to 1,000 μm (specifically, particle diameter of 106 to 1,000 μm) were selected by the above-mentioned sieving, and 50 particles were randomly selected from these particles. The radius of curvature r i The radius R of the maximum inscribed circle was also determined, and the roundness P of each particle was calculated. The average value PA of the roundness P of 50 particles was calculated and used as the average roundness.
[0047] [Repose angle of resin powder] The resin powder was conditioned for one week under an atmosphere of 20°C and 30% RH or 20°C and 65% RH. Thereafter, the angle of repose of the resin powder was measured using a multi-tester MT-1001 manufactured by Seishin Enterprise Co., Ltd. The angle of repose was measured according to the method described in JIS 9301-2-2:1999. The inventors have confirmed that the smaller the angle of repose of a resin powder, the better the passability through pipes and silos.
[0048] [Example 1] Preparation of PVA1 resin powder 1 A 250L reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet, and an initiator addition port was charged with 112.5 kg of vinyl acetate and 37.5 kg of methanol (vinyl acetate 75% by mass: methanol 25% by mass), and the system was replaced with nitrogen for 30 minutes while bubbling with nitrogen. The temperature of the reactor was started to rise, and when the internal temperature reached 60°C, 35 g of 2,2'-azobisisobutyronitrile (AIBN) was added to start polymerization, and when the polymerization rate reached 50%, the reactor was cooled to terminate the polymerization. The solid concentration at the time of termination of polymerization was 37.0% by mass. Subsequently, unreacted vinyl acetate monomer was removed at 30°C under reduced pressure while occasionally adding methanol, to obtain a methanol solution of polyvinyl acetate (PVAc) (concentration 35% by mass). Further, 1.86 kg of an alkaline solution (10 mass% methanol solution of sodium hydroxide) was added to the methanol solution of PVAc prepared by adding methanol to the mixture (PVAc concentration in the saponification solution: 30%, molar ratio of sodium hydroxide to vinyl acetate units in PVAc: 0.02) to perform saponification. After adding the alkaline solution, a gel-like substance (resin solid) was formed about 1 minute, and this was pulverized in a pulverizer. The pulverized substance was left at 40°C for 1 hour to allow saponification to proceed, and then 50 kg of methyl acetate was added to neutralize the remaining alkali. After confirming that neutralization was complete using a phenolphthalein indicator, the mixture was filtered to obtain a white solid, to which 200 kg of methanol was added and left to wash at room temperature for 3 hours. The above washing operation was repeated three times, and the white solid obtained by centrifugal deliquification was left in a dryer at 65°C for 2 days to obtain a crude powder of PVA1. The polymerization degree of PVA1 was 1,700, and the saponification degree was 98.5 mol%. Next, the coarse powder of PVA1 was loaded into a Loedige mixer "FKM130D" equipped with a Becker-type shovel manufactured by Chuo Kiko Co., Ltd. Surface treatment was carried out for 3 hours at room temperature in a nitrogen atmosphere at a rotation speed of 160 rpm. This resulted in resin powder 1 with an average particle size of 650 μm and an average roundness of 0.25.
[0049] [Examples 2 to 10, 15 to 16] Resin powder 2 of PVA2 and the like were obtained in the same manner as in Example 1 except that the conditions shown in Table 1 were used.
[0050] [Example 11] A 250L reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet, a comonomer dropping port, and an initiator addition port was charged with 120.0 kg of vinyl acetate and 30.0 kg of methanol (80% by mass of vinyl acetate: 20% by mass of methanol), and the system was replaced with nitrogen for 30 minutes while bubbling with nitrogen. The temperature of the reactor was started to rise, and when the internal temperature reached 60°C, 2.5 kg of acetaldehyde and 35 g of 2,2'-azobisisobutyronitrile (AIBN) were added to start polymerization, and when the polymerization rate reached 50%, the reactor was cooled to stop the polymerization. The solid content concentration at the time of stopping the polymerization was 39.3% by mass. The following was performed in the same manner as in Example 1, except that the conditions were as shown in Table 1, to obtain a resin powder 11 of PVA11.
[0051] [Example 12] Polymerization and saponification were carried out in the same manner as in Example 2 described in JP2019-011282A, to obtain a crude powder of ethylene-modified PVA (PVA12) having a degree of polymerization of 1850, a degree of saponification of 98.5 mol%, and an ethylene unit content of 6 mol%. The following procedures were carried out in the same manner as in Example 1, except that the conditions were as shown in Table 1, to obtain a resin powder 12 of PVA12.
[0052] [Example 13] A 250L reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet, a comonomer dropping port, and an initiator addition port was charged with 112.5 kg of vinyl acetate, 37.5 g of methanol (75% by mass of vinyl acetate: 25% by mass of methanol), and 220 ml of a methanol solution in which methyl methacrylate was dissolved at 24% by mass, and the system was replaced with nitrogen for 30 minutes while bubbling with nitrogen. The temperature of the reactor was started to rise, and when the internal temperature reached 60°C, 25 g of 2,2'-azobisisobutyronitrile (AIBN) was added to start polymerization, and while gradually adding 11 L of the above methanol solution of methyl methacrylate, the polymerization was stopped by cooling when the polymerization rate reached 40%. The solid content concentration at the time of polymerization termination was 28.0% by mass. The following was obtained in the same manner as in Example 1 except that the conditions in Table 1 were used.
[0053] [Example 14] Resin powder 14 of PVA14 was obtained in the same manner as in Example 2, except that the pulverization with the pulverizer was carried out more coarsely than in Example 1.
[0054] [Examples 17 to 19] Resin powder 17 of PVA17 and the like were obtained in the same manner as in Example 2, except that the surface treatment was performed using the device shown in Table 1 instead of the Loedige mixer.
[0055] [Comparative Example 1] Resin powder 1' of PVA1' was obtained in the same manner as in Example 2, except that the pulverization with the pulverizer was carried out more coarsely than in Example 14.
[0056] [Comparative Example 2] Resin powder 2' of PVA 2' was obtained in the same manner as in Example 2, except that the surface treatment using the Loedige mixer was not carried out.
[0057] Table 2 shows the degree of polymerization and degree of saponification of each PVA obtained in Examples 1 to 19 and Comparative Examples 1 and 2, the average roundness, average particle size, and content of particles with a particle size of 100 to 1,000 μm of each resin powder, as well as the product of the average roundness and the degree of saponification.
[0058] [evaluation] The angle of repose of each of the resin powders obtained in Examples 1 to 19 and Comparative Examples 1 and 2 was measured by the above method after humidity conditioning in an atmosphere of 20° C. and 30% RH and 20° C. and 65% RH. The measurement results are shown in Table 2.
[0059] [Table 1]
[0060] [Table 2]
[0061] As shown in Table 2, the resin powders of Examples 1 to 19 had angles of repose of less than 38° after humidity conditioning in an atmosphere with a humidity of 30% RH, and angles of repose of less than 40° in an environment with a humidity of 65% RH. It was confirmed that the resin powders of Examples 1 to 19 had small angles of repose and excellent passability through pipes and silos. On the other hand, the resin powder of Comparative Example 1, which had a large average particle size, and the resin powder of Comparative Example 2, which had a small average roundness, had large angles of repose.
[0062] For example, comparing Examples 1 to 5, it is found that in a high humidity environment, the degree of saponification of PVA has a large effect on the angle of repose. The resin powders of Examples 1 to 3, 6 to 9, 11 to 13, 15 and 17, which have a product of the average roundness and the degree of saponification of 18 mol % or more and an average particle size of 100 to 1,000 μm, have an angle of repose of less than 38° after humidity conditioning in an atmosphere of 65% RH, and have particularly excellent passability even under high humidity. [Industrial Applicability]
[0063] The resin powder of the present invention can be used for various applications such as synthetic fiber raw materials, film raw materials, emulsifying dispersants, and adhesives.
Claims
1. The particle contains a vinyl alcohol polymer and has an average particle size of 100 to 2,000 μm. The average value PA of the roundness P represented by the following formula (1) of 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm is 0.1 to 0.8, The resin powder has a proportion of monomer units other than vinyl alcohol units and vinyl ester units of 10 mol % or less based on all monomer units in the vinyl alcohol polymer. [0010] (In formula (1), r i is the radius of curvature for each corner of the particle. R is the radius of the maximum inscribed circle of the particle. N is the number of corners the particle has. However, if the number of corners of a particle is 9 or more, the radii of curvature of the 8 corners in ascending order of the radius of curvature are used, and N is 8.)
2. 2. The resin powder according to claim 1, wherein the vinyl alcohol polymer has a viscosity average degree of polymerization of 200 to 5,000 and a degree of saponification of 35 to 99.99 mol %.
3. The resin powder according to claim 1 or 2, which satisfies the following formula (2) and has an average particle size of 100 to 1,000 μm: P A × S ≧ 18 (2) (In formula (2), S is the degree of saponification (mol %) of the vinyl alcohol polymer.)
4. The resin powder according to any one of claims 1 to 3, wherein the content of particles having a particle diameter of 100 to 1,000 µm is 50 mass % or more.
5. A method for producing a resin powder comprising a vinyl alcohol polymer, the resin powder having an average particle size of 100 to 2,000 μm, and an average value PA of roundness P represented by the following formula (1) of 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm being 0.1 to 0.8, A step of obtaining a coarse powder by pulverizing a resin solid material containing a vinyl alcohol polymer; A step of processing the surface of the coarse powder A method for producing a resin powder comprising the steps of: [0025] (In formula (1), r i is the radius of curvature for each corner of the particle. R is the radius of the maximum inscribed circle of the particle. N is the number of corners that the particle has. However, if the number of corners of a particle is 9 or more, the radii of curvature of the 8 corners in ascending order of the radius of curvature are used, and N is 8.)
6. A method for producing a resin powder comprising a vinyl alcohol polymer, the resin powder having an average particle size of 100 to 2,000 μm, and an average value PA of roundness P, expressed by the following formula (1), of 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm, being 0.1 to 0.8, A process for obtaining a coarse powder by pulverizing a resin solid material containing a vinyl alcohol polymer. A method for producing a resin powder comprising the steps of: [0030] (In formula (1), r i is the radius of curvature for each corner of the particle. R is the radius of the maximum inscribed circle of the particle. N is the number of corners that the particle has. However, if the number of corners of a particle is 9 or more, the radii of curvature of the 8 corners in ascending order of the radius of curvature are used, and N is 8.)
Citation Information
Patent Citations
Water-soluble composite containing thermoplastic PVA (polyvinyl alcohol) and preparation method of water-soluble composite containing thermoplastic PVA
CN107266838A
Method for rapidly preparing monodisperse polyvinyl alcohol microspheres at normal temperature
CN109988323A
Dissolution method of granules
JP2006205071A
Pearl like polyvinyl alcohol particles, production process thereof, and temporary vascular embolic agent
JP2009256641A
Adsorbent
JP2016209836A